Estudo longitudinal sobre representações sociais da epilepsia - Gouveia, Maria Lucrécia de Aquino (2024)
Introduction : Epilepsy is an electrophysiological disorder with variable clinical manifestations. According to estimates by the World Health Organization, between 4 and 10 people in every thousand have epilepsy. Social representations refer to explanations, beliefs and ideas that allow us to evoke a given object, person or event, with the aim of explaining human phenomena from a collective perspective, without losing sight of their individuality. Objectives : to identify the social representations developed by people with epilepsy, family members of people with epilepsy and people without epilepsy; to verify the existence of divergences or consensuses in social representations among people with epilepsy, family members of people with epilepsy and people without epilepsy, analyzing the importance of the functions of the theory of social representations in professional practice, in daily life and in health, based on two studies; comparing the social representations about epilepsy in the studies. Method : this is an observational longitudinal study carried out with ninety people: forty-five in the first study and forty-five in the second: 15 people with epilepsy; 15 family members of people with epilepsy and 15 people without epilepsy, in the first study and in the second study, totaling 90 people. The data from the second study were organized into a corpus and submitted to textual analysis and processed with the aid of the IRaMuTeQ software , version 0.7 alpha 2 (Interface de R pourles Analyses Multidimensionnelles de Textes et de Questionnaires); the data from the first study were analyzed using the categorical content analysis technique, corresponding to the same analysis procedure used by the software; the second study followed the steps: construction of the corpus ; composition of the units of analysis; analysis procedures; categorization and description of the categories. The results of both studies were interpreted according to the theory of Social Representations. Results and Discussion : the data from the studies indicated five classes, defined nominally the same in both studies: class 1: manifestation/description (relational, explanatory, psychosocial and organic/physical); class 2: beliefs (supernatural and naturalistic); class 3: causes (transmissible/contagion, traumatic/physical, psycho-sociocultural, biological/genetic and spiritual); class 4: treatment (medical, psychosocial and alternative); class 5: feelings (positive and negative). Comparing the two studies, similar social representations are observed in both studies, for example: the presence of stigmatizing and prejudiced content in both studies, when talking about epilepsy, both by people with epilepsy and by family members and people without epilepsy. They consider epilepsy a disease; however, in the first study, a strong association with contagion was identified; while in the second study, this association was not identified. Final considerations : the results indicate that the stigma of the disease still remains today. This scientific knowledge for the construction of SR on epilepsy may have a positive impact on the social representations of health professionals and the general population.